Principled Pluralism Sebagai Model Ideal Hubungan Agama Dan Konstitusi Di Indonesia - Rifdah, Haliza Nur (Universitas Brawijaya, 2023)
As a plural country, Indonesia needs to know the relationship between religion and its constitution. Even though it has been written in Article 29 (1) of the 1945 Constitution of the Republic of Indonesia, the connection is still vague. It shows in its practice where there are still injustice actions that have been experienced by minorities, such as demolition of churches or forced conversion to one specific religion. Neglecting this relationship is undoubtedly dangerous because religion and the constitution influence social life. Therefore, by using doctrinal research methods and historical and comparative legal approaches, this study aims to find the classification of these relationships and the ideal model for Indonesia. The study shows the relationship is in the form of pluralist accommodation, where this form upholds religious values and acknowledges the existence of various religions and beliefs in society. To strengthening this relationship, principled pluralism is considered an ideal model in Indonesia.